Disaster complexity and the Santiago de Compostela train derailment. Issue 1 (2nd January 2016) - Shultz, James M.; Garcia-Vera, Maria Paz; Santos, Clara Gesteira; Sanz, Jesús; Bibel, George; Schulman, Carl; Bahouth, George; Dias Guichot, Yasmin; Espinel, Zelde; Rechkemmer, Andreas
ABSTRACT: This disaster complexity case study examines Spain's deadliest train derailment that occurred on July 24, 2013 on the outskirts of Santiago de Compostela, Galicia, Spain. Train derailments are typically survivable. However, in this case, human error was a primary factor as the train driver powered the Alvia train into a left curve at more than twice the posted speed. All 13 cars came off the rails with many of the carriages careening into a concrete barrier lining the curve, leading to exceptional mortality and injury. Among the 224 train occupants, 80 (36%) were killed and all of the remaining 144 (4%) were injured. The official investigative report determined that this crash was completely preventable.